Tubularized parameatal based dartos-spongiosum flap urethroplasty in distal hypospadias with flat glans, shallow meatal groove, and severe glans tilt - Singh, Chandra Shekhar; Kunnur, Vijaymahantesh S; Kunnur, Shanthala V; Kunnur, Anil Kumar S (Indian Journal of Child Health, 2016)
Objective: To report the technique and results of single stage tubularized parameatal based dartos-spongiosum flap urethroplasty for distal hypospadias with flat glans, shallow meatal groove, and severe glans tilt. Materials and Methods: The study was conducted over a period of 2-year from October 2013 to October 2015, and 19 patients with distal hypospadias were included in the study with flat glans, poor urethral groove, and severe glans tilt, who otherwise would have been subjected to transection of urethral plate and a two-stage procedure. In this technique, bilateral flaps were fashioned along the preputial edge beginning from the hypospadiac meatus with intact dartos, keeping the base of the flaps attached to the bifurcated spongiosum. The urethral plate was transected. Glans was split wide open. Bilateral flaps joined at ventral midline creating new urethral plate which was tubularized with the creation of slit like wide meatus at the tip of glans. Neourethral coverage was provided with double dartos flap. Complications and aesthetic appearance on a score of 1-10 were outcome measures. Results: There was no urethral stricture, residual chordee, penile rotation, or asymmetrical penis. The average aesthetic score was 8.5. Meatus was at the tip of glans with adequate caliber in all patients. Two (10.5%) out of 19 patients developed subcoronal fistula that required surgical closure. Conclusion: Tubularized parameatal-based dartos-spongiosum flap urethroplasty is viable and easy to reproduce option for management of a specific group of patients with distal hypospadias (with flat glans, poor urethral plate, and glans tilt) and is associated with very low complication rate.